2011
DOI: 10.1016/j.foodres.2011.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Exotic fruits as therapeutic complements for diabetes, obesity and metabolic syndrome

Abstract: The prevalence and severity of obesity, type 2-diabetes, and the resultant metabolic syndrome are rapidly increasing. As successful preventive and therapeutic strategies for these life-threatening health ailments often come with adverse side effects, nutritional elements are widely used in many countries as preventive therapies to prevent or manage metabolic syndrome. Fruits are important dietary components, and contain various bioactive constituents. Many of these constituents have been proven to be useful to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
119
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(125 citation statements)
references
References 92 publications
(109 reference statements)
2
119
0
4
Order By: Relevance
“…Glycemia, total cholesterol, HDL-c (high density lipoprotein cholesterol), LDL-c (low density lipoprotein Some studies have shown that the consumption of dietary fiber may reduce the risk of diseases and can prevent hyperlipidemias, cardiovascular diseases, diabetes, and obesity (DEVALARAJA; JAIN; YADA, 2011;PAPATHANASOPOULOS, CAMILLERI, 2010;PAIVA, 2008). The ingestion of dietary grains and fibers has been associated with diminished risk for obesity and diabetes (QI et al, 2010;JANG et al, 2010;ASLAM et al, 2009;GRASSI et al, 2008).…”
Section: Biochemical Measurementsmentioning
confidence: 99%
“…Glycemia, total cholesterol, HDL-c (high density lipoprotein cholesterol), LDL-c (low density lipoprotein Some studies have shown that the consumption of dietary fiber may reduce the risk of diseases and can prevent hyperlipidemias, cardiovascular diseases, diabetes, and obesity (DEVALARAJA; JAIN; YADA, 2011;PAPATHANASOPOULOS, CAMILLERI, 2010;PAIVA, 2008). The ingestion of dietary grains and fibers has been associated with diminished risk for obesity and diabetes (QI et al, 2010;JANG et al, 2010;ASLAM et al, 2009;GRASSI et al, 2008).…”
Section: Biochemical Measurementsmentioning
confidence: 99%
“…Durian is rich in carbohydrates, proteins, fats, minerals and vitamins (Bai-Ngew et al, 2014). Durian pulp contains vitamin C of 19.7 mg 100 g −1 , some vitamins of the B complex and β-carotene (23 Âľg 100 g −1 ) (Devalaraja et al, 2011). However, the market of durian is restricted due to its fruiting season, difficulty in transportation (only certain regions have good quality durian) and shelf life, which is limited to only 2 to 5 days at room temperature (Anabesa et al, 2006;Chin et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The potential health benefits of tropical fruits have aroused worldwide interest and created space in the international market for exotic fruits [89,90]. By definition, exotic fruits do not originate in the country where they presently occur.…”
Section: Macronutrient and Caloric Content Of Cubiu Fruit Tissues Durmentioning
confidence: 99%
“…Predictably, exotic fruits were once restricted to people living in limited geographic areas, but have now become common in other countries [91]. This growing interest in exotic fruits is in part due to the high prevalence of nutritional disorders (e.g., obesity, metabolic syndrome, diabetes mellitus, and hidden hunger or micronutrient malnutrition), and an urgent need for new therapeutic avenues [90,92]. Accordingly, Brazilian farmers have been cultivating cubiu fruits to export to Japan for the extraction of functional food ingredients such as pectin [7,8].…”
Section: Macronutrient and Caloric Content Of Cubiu Fruit Tissues Durmentioning
confidence: 99%